2021
DOI: 10.1093/jpp/rgab129
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic efficacy of pachymic acid in chronic kidney disease induced in rats: role of Wnt/β-catenin/renin–angiotensin axis

Abstract: Objectives Chronic kidney disease (CKD) is a major public health problem associated with high mortality. The therapeutic effects of pachymic in CKD management and its underlying mechanisms have not been studied. Therefore, we aimed to investigate the possible inhibitory effect of PA on renal Wnt/β-catenin signalling in CKD. Methods CKD was induced in rats by doxorubicin (DOX; 3.5 mg/kg i.p., twice weekly for 3 weeks). Rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Ginsenoside (Rg1, Rg2, Rg3, etc.) [ 16 18 ], paeonol [ 19 , 20 ], gallic acid [ 21 ], loganin [ 22 ] and pachymic acid [ 23 ] showed activities in kidney fibrosis and other kidney diseases. Cornuside [ 24 ], loganic acid [ 25 ] and rehmannioside A [ 26 ] have anti-inflammatory activities, which further proved that the key constituents in the “constituents-targets-pathways” network may be used as the pharmacodynamic material basis of RSGB in the treatment of renal fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Ginsenoside (Rg1, Rg2, Rg3, etc.) [ 16 18 ], paeonol [ 19 , 20 ], gallic acid [ 21 ], loganin [ 22 ] and pachymic acid [ 23 ] showed activities in kidney fibrosis and other kidney diseases. Cornuside [ 24 ], loganic acid [ 25 ] and rehmannioside A [ 26 ] have anti-inflammatory activities, which further proved that the key constituents in the “constituents-targets-pathways” network may be used as the pharmacodynamic material basis of RSGB in the treatment of renal fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the fibrosis percentage, the Masson's trichrome-stained sections were captured at ×200 magnification, where the blue color indicated collagen deposition. 32,40–43…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the fibrosis percentage, the Masson's trichrome-stained sections were captured at ×200 magnification, where the blue color indicated collagen deposition. 32,[40][41][42][43] The paraffin-embedded heart sections were also used for immunohistochemical staining of CD31. The heart sections were deparaffinized with xylene and rehydrated with ethanol.…”
Section: Histological Analysismentioning
confidence: 99%
“…Gui et al ( 64 ) reported that PA alleviates LPS-induced lung injury by relieving LPS-inflammation, such as TNF-α, IL-6, monocyte chemoattractant protein 1 and IL-1β, reducing cell numbers in bronchoalveolar lavage fluid, and inhibiting LPS-induced apoptosis. Additionally, PA ameliorates renal injury in vivo by inhibiting renal inflammation, reducing the levels of TNF-α, IL-6 and inducible nitric oxide synthase, enhancing the expression of Nrf2 and HO-1, and preventing renal Wnt/β-catenin signaling ( 65 , 66 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…PA alone or as adjuvant therapy with losartan can lower serum B-type natriuretic peptide and improve systolic function and cardiac fiber diameter to attenuate doxorubicin-induced heart failure in vivo ( 86 ). Moreover, PA ameliorates doxorubicin-induced renal injury by regulating of serum cystatin-C, urine albumin/creatinine ratio, renal podocin and klotho content, TNF-α, IL-6 and IL-1β ( 66 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%